THE IMPLEMENTATION OF LEARNING STRATEGIES ACCORDING TO LEARNING STYLES AND THE RELATIONSHIP WITH UNDERGRADUATE MEDICAL STUDENTS’ ACADEMIC PERFORMANCES - Vera Liu; Yoanita Widjaja (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Each individual has his or her distinctive style of learning. Learning styles are the combination of the most effective and efficient ways a person chooses to focus on receiving and processing information from the environment. However, the knowledge of learning style alone will not make any changes to academic performance if it is not followed by changes in learning strategies tailored to one’s learning style. The suitability of learning strategies with learning styles is one of the important factors that can affect student's academic performance. Research on this topic is still rarely found today. Hence, the purpose of this study is to determine the relationship between the suitability of learning strategies and learning styles with the academic performances of undergraduate medical students of the Faculty of Medicine, Universitas Tarumanagara.Methods: This is an analytic study with a cross-sectional method that involved 227 undergraduate medical students of the Faculty of Medicine, Universitas Tarumanagara. Data were obtained through validated VARK 7.1 Indonesian questionnaires on learning styles and learning strategies consisting of a series of questions about the characteristics of each learning style from Fleming ND.Results: This study shows that 142 respondents (62,6%) implemented learning strategies that did not fit their learning styles and the rest 85 respondents (37,4%) implemented appropriate learning styles. Seventy-two out of 85 (84,7%) respondents show matching learning strategies and learning styles and they have good academic performances (GPA), while 104 of 142 students (73,2%) with unsuitable learning strategies and learning styles have good GPA as well with a p-value of 0,066 (p>0,05).Conclusion: There is no significant relationship between the suitability of learning strategies with learning styles and the academic performance of undergraduate medical students at Faculty of Medicine Universitas Tarumanagara.